A trait‐based approach to assessing resistance and resilience to wildfire in two iconic North American conifers. (16th August 2020) - Rodman, Kyle C.; Veblen, Thomas T.; Andrus, Robert A.; Enright, Neal J.; Fontaine, Joseph B.; Gonzalez, Angela D.; Redmond, Miranda D.; Wion, Andreas P.
Abstract: Ongoing changes in fire regimes have the potential to drive widespread shifts in Earth's vegetation. Plant traits and vital rates provide insight into vulnerability to fire‐driven vegetation shifts because they can be indicators of the ability of individuals to survive fire (resistance) and populations to persist (resilience) following fire. In 15 study sites spanning climatic gradients in the southern Rocky Mountains, USA, we quantified variation in key traits and vital rates of two co‐occurring, widely distributed conifers ( Pinus ponderosa Douglas ex. P. Lawson & C. Lawson and Pseudotsuga menziesii (Mirb.) Franco). We used mixed‐effects models to explain inter‐ and intraspecific variation in tree growth, survival, bark thickness and seed cone production, as a function of species, tree life stage (i.e. diameter, height and age), average climate, local competition and site conditions. Pinus ponderosa was predicted to survive low‐severity fire at a 23% earlier age than P. menziesii . Pinus ponderosa had thicker bark and more rapid juvenile height growth, traits conferring greater fire resistance. In contrast, P. menziesii was predicted to produce seed cones at a 28% earlier age than P. ponderosa . For both species, larger individuals were more likely to survive fire and to produce cones. For P. ponderosa, cone production increased where average actual evapotranspiration (AET) was higher and local competition was lower. More frequent cone production on productive sites with higher AET is an important and underappreciated mechanism that may help to explain greater resilience to fire in these areas. Synthesis . Our analyses indicated that many plant traits and vital rates related to fire differed between Pinus ponderosa and Pseudotsuga menziesii, with trade‐offs between investment in traits that promote individual defence to fire and those that promote recolonization of disturbed sites. Future changes in fire regimes will act as a filter throughout North American forests, with our findings helping to infer which individuals and populations of two iconic species are most vulnerable to future change and offering a framework for future inquiry in other forests facing an uncertain future. Abstract : Plant traits and vital rates differed among populations of Pinus ponderosa and Pseudotsuga menziesii, with apparent trade‐offs between investment in traits that promote individual defence to fire (e.g. bark thickness, time to fire‐resistant size) and those that promote recolonization of disturbed sites (e.g. seed cone production). Future changes in fire regimes will act as a filter throughout North American forests, with our findings helping to infer which individuals and populations of two iconic species are most vulnerable to future change and offering a framework for future inquiry in other forests facing an uncertain future.